(untitled) (Jurnal Teknologi Industri Pertanian, 2025)
Indonesia is the world’s largest coconut producer, with Indragiri Hilir being one of its major coconut-producing regencies. Despite the extensive coconut plantations in the region, the development of the coconut agroindustry remains underdeveloped. Coconut oil, a high-demand product in international markets, represents a significant opportunity for agroindustrial growth. Effective agroindustrial development requires accurate determination of raw material needs to plan production capacity and ensure efficient operation. Forecasting demand is a critical first step in this process, as it can enhance efficiency, reduce unnecessary raw material stockpiling, and minimise waste. This study aimed to forecast the demand for coconut oil, which is a crucial step for determining raw material requirements in the development of the coconut oil agroindustry. The research integrated ARIMA and mass balance methods. The findings indicated that coconut oil demand was projected to reach 556,749 tons per year from 2025 to 2030, with a corresponding raw material requirement of 4,259,130 tons per year. This study provides valuable insights for both farmer and agroindustry stakeholders in advancing the development of the coconut oil agroindustry. Keywords: agroindustry development, coconut oil, demand forecasting, raw material